Single Domain Antibodies Methods and Protocols - Saerens, Dirk.; Saerens, Dirk.; Muyldermans, Serge.; Muyldermans, Serge. (Methods in Molecular Biology, 2012)
The development of the hybridoma technology created the possibility to obtain unlimited amounts of monoclonal antibodies (mAb) with high specificity and affinity for any target and to introduce mAbs in a wide range of applications; however, the bulky size of mAbs, costly production, and cumbersome engineering hampered regularly their streamlined development in some applications.  In Single Domain Antibodies: Methods and Protocols, expert researchers examine single variable domain antibody fragments, referred to as VH, VL, VHH or VNAR. These fragments are the smallest intact antigen-binding fragments that can be produced recombinantly at low cost.  Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.